Partnership dissolution, complementarity, and investment incentives - Jianpei Li; Elmar Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2004)
We study a partnership that anticipates its possible dissolution. In our model, partnerships form in order to take advantage of complementary skills; although new opportunities may arise that make partners? skills useless. We characterize the optimal, incentive-compatible partnership contract that can be implemented by a simple call option, and then analyze the commonly used buy'sell provision. We show that this dissolution rule gives rise to inefficiency, either in the form of excessive dissolutions combined with underinvestment or efficient dissolutions combined with overinvestment. However, supplementing the buy'sell provision with the right to veto may restore efficiency.
Keywords: L24; J12; D82; K12; C78; 330; Partnerschaftsgesellschaft; Anreizvertrag; Realoption; Qualifikation; Theorie